Oral intake of xanthohumol attenuates lipoteichoic acid-induced inflammatory response in human PBMCs - Jung, Finn; Staltner, Raphaela; Tahir, Ammar; Baumann, Anja; Burger, Katharina; Halilbasic, Emina; Hellerbrand, Claus; Bergheim, Ina (European Journal of Nutrition, 2022)
Purpose The aim of the study was to determine if xanthohumol, a prenylated chalcone found in Hop (Humulus lupulus), has anti-inflammatory effects in healthy humans if applied in low doses achievable through dietary intake. Methods In a placebo-controlled single-blinded cross-over design study, 14 healthy young men and women either consumed a beverage containing 0.125 mg xanthohumol or a placebo. Peripheral blood mononuclear cells (PBMCs) were isolated before and 1 h after the intake of the beverages. Subsequently, PBMCs were stimulated with or without lipoteichoic acid (LTA) for 24 and 48 h. Concentrations of interleukin-1 beta (IL-1 beta), interleukin-6 (IL-6) and soluble cluster of differentiation (sCD14) protein were determined in cell culture supernatant. Furthermore, hTLR2 transfected HEK293 cells were stimulated with LTA in the presence or absence of xanthohumol and sCD14. Results The stimulation of PBMCs with LTA for 24 and 48 h resulted in a significant induction of IL-1 beta, IL-6, and sCD14 protein release in PBMCs of both, fasted subjects and subjects after the ingestion of the placebo. In contrast, after ingesting xanthohumol, LTA-dependent induction of IL-1 beta, IL-6, and sCD14 protein release from PBMCs was not significantly higher than in unstimulated cells after 48 h. In hTLR2 transfected HEK293 cells xanthohumol significantly suppressed the LTA-dependent activation of cells, an effect attenuated when cells were co-incubated with sCD14. Conclusion The results of our study suggest that an ingestion of low doses of xanthohumol can suppress the LTA-dependent stimulation of PBMCs through mechanisms involving the interaction of CD14 with TLR2. Study registered at ClinicalTrials.gov (NCT04847193, 22.03.2022).
CRIS-Team WoS Importer:2022-07-29